2020
DOI: 10.1590/0103-6440202003207
|View full text |Cite
|
Sign up to set email alerts
|

In-Vitro Model of Scardovia wiggsiae Biofilm Formation and Effect of Nicotine

Abstract: Recently, Scardovia wiggsiae has been reported to be strongly associated with caries formation. This study aimed to establish an in vitro model of S. wiggsiae biofilm and to investigate the effect of nicotine on S. wiggsiae colony-forming units (CFUs) growth. S. wiggsiae biofilm was grown overnight using brain-heart infusion (BHI) broth supplemented with 5 g of yeast extract/L (BHI-YE). The overnight culture was used as an inoculum to grow S. wiggsiae biofilm on standardized enamel and dentin samples. Samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The nicotine concentrations used in the present study were 0 (control), 1, and 2 mg/mL, similar values found in human saliva of smokers 40) . Although it has been reported that high concentrations of nicotine can cause an increase in biofilm formation [41][42][43] , CHXdoped thin film effectively suppressed such upregulating effect. Consistently, significant decreases were found in the absorbance values in the spectrophotometer assay when comparing CHX-doped thin film with the control surfaces.…”
Section: Discussionmentioning
confidence: 92%
“…The nicotine concentrations used in the present study were 0 (control), 1, and 2 mg/mL, similar values found in human saliva of smokers 40) . Although it has been reported that high concentrations of nicotine can cause an increase in biofilm formation [41][42][43] , CHXdoped thin film effectively suppressed such upregulating effect. Consistently, significant decreases were found in the absorbance values in the spectrophotometer assay when comparing CHX-doped thin film with the control surfaces.…”
Section: Discussionmentioning
confidence: 92%